2007
DOI: 10.1210/jc.2006-2861
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay and Tandem Mass Spectrometry Measurement of Bedtime Salivary Cortisol Levels: A Comparison of Assays to Establish Hypercortisolism

Abstract: Salivary cortisol levels should not be used as the sole test to diagnose Cushing's syndrome if laboratory-provided reference ranges are used for diagnostic interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
2
7

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 15 publications
7
86
2
7
Order By: Relevance
“…The study by Beko et al revealed better performance of LSC using ECLIA (sensitivity 100% and specificity 88%) compared to RIA (sensitivity 100% and specificity 71%) [23]. Another study demonstrated an important rate of abnormal LSC results in volunteers without evidence of Cushing's syndrome when measured using two different commercial assays and evaluated with laboratory provided normative ranges [24]. Assays of RIA and ELISA can be affected by cross-reactivity with cortisol metabolites and synthetic glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Beko et al revealed better performance of LSC using ECLIA (sensitivity 100% and specificity 88%) compared to RIA (sensitivity 100% and specificity 71%) [23]. Another study demonstrated an important rate of abnormal LSC results in volunteers without evidence of Cushing's syndrome when measured using two different commercial assays and evaluated with laboratory provided normative ranges [24]. Assays of RIA and ELISA can be affected by cross-reactivity with cortisol metabolites and synthetic glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, reported cut-off values differ considerably. Depending on the relative cross-reactivity of cortisol antibodies towards cortisone, there could be quite variable values for salivary cortisol measured by different immunoassays (Baid et al, 2007). Measurement by LC-MS/MS can overcome this problem.…”
Section: Lc-ms/ms Enables the Simultaneous Determination Of Cortisol mentioning
confidence: 99%
“…More recently, liquid chromatography-tandem mass spectrometry (LC-MS/MS) measurement of salivary cortisol has been also available commercially (49,50). RIA and LC-MS/MS measurement of salivary cortisol and their accuracy of reference ranges were compared, in a cross-sectional prospective study of outpatients, in healthy volunteers and obese subjects with cushingoid features (49).…”
Section: Late-night Salivary Cortisolmentioning
confidence: 99%
“…RIA and LC-MS/MS measurement of salivary cortisol and their accuracy of reference ranges were compared, in a cross-sectional prospective study of outpatients, in healthy volunteers and obese subjects with cushingoid features (49). This study demonstrated an important rate of abnormal bedtime salivary cortisol, measured in two different commercial assays and evaluated with laboratory provided normative ranges.…”
Section: Late-night Salivary Cortisolmentioning
confidence: 99%
See 1 more Smart Citation